Photoelectrochemical properties of sol-gel Nb2O5 films - Barros, D. D.; Abreu, P. P.; Werner, U.; Aegerter, M. A. (Kluwer Academic Publ, 1997)
Structural, optical, electro and photoelectrochemical properties of amorphous and crystalline sol-gel Nb2O5 coatings have been determined. The coatings are n-type semiconductor with indirect allowed transition and present an overall low quantum efficiency (phi < 4%) for UV light to electric conversion. The photoconducting behavior of the coatings is discussed within the framework of the Gartner and Sodergren models. Improvement can be foreseen if Nb2O5 coatings can be made of 10-20 nm size nanoparticles.
Keywords: sol-gel; Nb2O5; film; photoconductivity; photoelectrochemistry; semiconductor; solar cell